Factors Influencing Age at Menarche, a School-Based Cross-Sectional Study - Novalia Kridayanti Novalia; Hery Sumasto; Nurlailis Saadah; Nani Surtinah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The last few years have seen the increasingly young age of menarche in teenagers. The average age of the national menarche from year to year is declining. The more children experience early menarche, the greater the risk of negative implications such as lack of personal hygiene, breast cancer, and early pregnancy. Menarche's age is influenced by nutritional, economic, pornographic, and genetic status. The purpose of this study was to determine the factors that affect menarche in adolescents aged 10-12 years. The research conducted is descriptive-analytic with a cross-sectional design. The population of MIN 3 Magetan students aged 10-12 years who have menstruated and have met the inclusion and exclusion criteria. The study sample was 87 respondents with a purposive sampling technique. Data collection using questionnaires. Statistical calculations are carried out by statistical and descriptive analysis with binary logistic regression tests. The average age of menarche is 11 years with the youngest age being 9 years and the oldest at 12 years, most female students experience early menarche (65.5%). There is an effect of nutritional status on menarche (p =0.048, Exp (B)= 4.3), there is an economic influence on menarche (p=0.000, Exp (B)= 11.3), there is an influence of pornographic exposure on menarche (p=0.001, Exp (B)= 12.1), and there is no genetic or age influence maternal menarche against menarche (0.388). Nutritional status, economic status, and exposure to pornographic media increase the incidence of early menarche. The highest risk factors for exposure to pornography resulted in 12.1 times the incidence of early menarche, economic status by 11.3 times, and nutritional status by 4.2 times. Strict supervision of mass media access and maintaining nutritional intake are necessary to prevent early menarche.